Kids' funniest knock-knocks - Keller, Charles; Sinclair, Jeff (New York : Sterling Pub., 2001)
The funniest knock-knocks ever! Give yourself and everyone else a good case of the giggles every time you tell jokes.
Includes index.
6 - 12 years
Keywords: Knock-knock jokes. -- Juvenile Literature; Wit and humor. -- Juvenile Literature